Improving Competencies for the Courier Service Industry in Malaysia - Hoo, Yee Hui; Fernando, Yudi (IGI Global USA, 2018)
The aim of this chapter is to explore the literature on improving competencies for the courier service industry in Malaysia. The use of internet and advancement in technologies enable e-commerce to quickly emerge in courier service industry, linking enterprises, associations, governments and individuals together. The usage of internet has changed the industry strategy in conducting business. It is crucial for a business to reassess their competencies to operate in a competitive global working environment which is highly volatile and rapidly change. Subsequently, the supply chain is facing a paradigm change in the e-business environment. A company supply chain in an e-business environment can be very complicated typically in Asia Market due to Asia Market is made up of many countries which is vary in culture, religion, political system, legal systems, language and stage of economic development.